Giant Coronary Artery Aneurysm After Breast Radiation in a Patient With Congenital Coronary Arteriovenous Fistula - Andrew Engel-Rodriguez; Natalie Engel-Rodriguez; Robert Engel-Rodriguez; Robert Engel-Ramos (Annals of Internal Medicine: Clinical Cases)
An 84-year-old Hispanic woman with medical history of coronary artery disease, hypertension, breast cancer, and left circumflex coronary artery ectasia with arteriovenous fistula to the coronary sinus was found with a new giant obtuse marginal 1 (OM1) saccular aneurysm measuring 8.4 × 6.5 cm on gated computed tomography angiogram 15 years after the first coronary angiogram. Coronary artery aneurysms are unusual anomalies that are encountered in 0.3% to 4.9% of patients who undergo coronary angiography. The incidence of giant coronary artery aneurysm is reported at 0.02% and we are not aware of any reports of OM1. Here, we report an extremely rare case of a OM1 giant coronary artery aneurysm.